2014
DOI: 10.1152/ajpendo.00578.2013
|View full text |Cite
|
Sign up to set email alerts
|

Loss ofPgc-1αexpression in aging mouse muscle potentiates glucose intolerance and systemic inflammation

Abstract: Diabetes risk increases significantly with age and correlates with lower oxidative capacity in muscle. Decreased expression of peroxisome proliferator-activated receptor-γ coactivator-1α ( Pgc-1α) and target gene pathways involved in mitochondrial oxidative phosphorylation are associated with muscle insulin resistance, but a causative role has not been established. We sought to determine whether a decline in Pgc-1α and oxidative gene expression occurs during aging and potentiates the development of age-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 58 publications
(71 reference statements)
2
62
1
1
Order By: Relevance
“…Glucose intolerance and increased blood pressure represent hallmarks of the age‐related metabolic syndrome (Hildrum, Mykletun, Hole, Midthjell, & Dahl, 2007). In line with the aggravated glucose intolerance in old mKO animals described previously (Sczelecki et al., 2014), we observed that absence of muscle PGC‐1α accelerated glucose intolerance during aging. Even though no overt amelioration in glucose tolerance was observed in the mTG mice, overexpression of muscle PGC‐1α abolished the age‐associated increase in blood pressure.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Glucose intolerance and increased blood pressure represent hallmarks of the age‐related metabolic syndrome (Hildrum, Mykletun, Hole, Midthjell, & Dahl, 2007). In line with the aggravated glucose intolerance in old mKO animals described previously (Sczelecki et al., 2014), we observed that absence of muscle PGC‐1α accelerated glucose intolerance during aging. Even though no overt amelioration in glucose tolerance was observed in the mTG mice, overexpression of muscle PGC‐1α abolished the age‐associated increase in blood pressure.…”
Section: Discussionmentioning
confidence: 74%
“…The age of 21 months as starting point was chosen based on the presarcopenic state of mice at that age, and to avoid a potential reduction in lifespan of the PGC‐1α knockout mice. While a number of effects of muscle‐specific gene ablation of PGC‐1α on muscle metabolism in aging have been demonstrated (Sczelecki et al., 2014), we now observed that reduced and elevated PGC‐1α levels accelerate and delay, respectively, broader aspects of muscle aging. Interestingly however, we also show that PGC‐1α modulation is not sufficient to fully control muscle aging as some age‐related muscle dysfunctions are not altered by deletion or overexpression of this coactivator.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Similarly, loss of PGC-1a, albeit in muscle, potentiates the pro-inflammatory environment of aging. 46 Therefore, as VWR increased PGC-1a in both iWAT and eWAT, it is possible that this may have mediated some of the protective effects we see against LPS induced inflammation. Clearly further work is needed to elucidate the mechanisms through which prior physical activity protects against LPS-induced inflammation.…”
Section: Discussionmentioning
confidence: 90%
“…Numerous studies have linked aging with development of insulin resistance (Rowe et al ., 1983; O'Shaughnessy et al ., 1992; Sczelecki et al ., 2013). In accord with this, we report a marked reduction in the ability of insulin to phosphorylate/activate PKB at its two key regulatory sites Thr 308 (by 1.7‐fold; P  < 0.05) and Ser 473 (by 1.6 fold; P  < 0.05) in aged versus young soleus tissue (Fig.…”
Section: Resultsmentioning
confidence: 99%